Community Involvement in the Implementation of Career Education. Monographs in Career Education - Hoyt, Kenneth B.; Office of Career Education (DHEW/OE), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
This monograph shares experiences of participants in a series of fifteen "miniconferences" for local K-12 career education coordinators held January-July 1979 regarding community involvement in the delivery of career education. Six sections describe specific examples of how particular communities have, to date, responded to a call for involvement of both the home/family structure and of the business/labor/industry/professional/government community. These responses include (1) informing community members about career education and selling the career education concept to the broader community; (2) organizing for effective community involvement in career education; (3) organizing community career education advisory boards; (4) other examples of community involvement in career education, including use of community persons as classroom resources, career education experiences provided by business/industry organizations, and "one on one" contacts between students and persons from the business/labor/industry community; and (5) involvement of community organizations in collaborative career education efforts. (YLB)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, DC 20402.
Educational level discussed: Elementary Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Advisory Committees; Career Education; Community Involvement; Community Organizations; Community Resources; Elementary Secondary Education; Government School Relationship; Professional Associations; Program Descriptions; Public Relations; Publicity; School Business Relationship; School Community Programs; School Community Relationship; Unions; Reports, Descriptive